Basic statistics for the behavioral science - Heiman, Gary W. ([Place of publication not identifed] : Cengage Learning Asia Pte Ltd, 2014)
The purpose of this book is to actively teach statistics. Author performed a page-by-page revision of the entire book, using knowledge of statistics and response to structured review of user and nonuser of the previous edition .
Chapter1. Introduction to statistics -- Chapter2. Statistics and the research process -- Chapter3. Frequency distribution and percentiles -- Chapter4. Measures of central tendency: The mean, median and mode -- Chapter5. Measures of variability: Range, variance and standard deviation -- Chapter6. z-Scores and the normal curve -- Chapter7. The correlation coefficient -- Chapter8. Linear regression - Halfway review -- Chapter9. Using probability to make decision about data -- Chapter10. Introduction to hypothesis testing -- Chapter11. Performing the one-sample t-test and testing correlation coefficient -- Chapter12. The two sample t-test -- Chapter13. The one-way analysis of variance -- Chapter14. The two-way analysis of variance -- Chapter15. Chi square and other nonparametric procedures - Second-halfway review .
Includes index.
Keywords: BEHAVIORAL SCIENCE